2010
DOI: 10.1117/1.3455507
|View full text |Cite
|
Sign up to set email alerts
|

Self-focusing and spherical aberrations in corneal tissue during photodisruption by femtosecond laser

Abstract: Abstract. The use of ultrashort pulse lasers is current in refractive surgery and has recently been extended to corneal grafting ͑kerato-plasty͒. When performing keratoplasty, however, permanent degradation of the optical properties of the patient's cornea compromises the penetration depth of the laser and the quality of the incisions, therefore causing unwanted secondary effects. Additionally, corneal grafting needs considerably higher penetration depths than refractive surgery. Little data are available abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…ThermoFisher) in an agar phantom. The NA is chosen to reduce the effects of spherical aberration, which can decrease the Strehl ratio as ablation depth is increased, 21 and to avoid self-focusing, which can cause damage before the intended focus or create a tighter focus, and lead to an underestimation of the ablation fluence threshold. 22,23 We ablate a 40 × 40 μm 2 FoV by scanning 512 lines at 1/16 frames per second, causing ∼0.078 μm separation between lines and ∼1.28 μm separation between pulses on the same line, resulting in a ∼20 pulse overlap.…”
mentioning
confidence: 99%
“…ThermoFisher) in an agar phantom. The NA is chosen to reduce the effects of spherical aberration, which can decrease the Strehl ratio as ablation depth is increased, 21 and to avoid self-focusing, which can cause damage before the intended focus or create a tighter focus, and lead to an underestimation of the ablation fluence threshold. 22,23 We ablate a 40 × 40 μm 2 FoV by scanning 512 lines at 1/16 frames per second, causing ∼0.078 μm separation between lines and ∼1.28 μm separation between pulses on the same line, resulting in a ∼20 pulse overlap.…”
mentioning
confidence: 99%
“…Although it has been shown that solid model systems such as gelatin or fused silica [34,35] are better suited than water [36], for example, they do not account for inhomogeneities of the corneal tissue and inter-subject variations [36,37]. Especially, nonlinear phenomena such as self-focusing depend critically on actual tissue properties and focusing conditions [36,38]. Furthermore, a recent study has shown that there is a difference in visual outcome between laser patterns which are centrifugally or centripetally applied [39].…”
Section: Discussionmentioning
confidence: 99%
“…The optical aberrations accumulate proportionally as the beam is focused deeper through the stromal layers,13 by nonlinear self-focusing effects 14. This jeopardises the laser efficacy at cutting and probably initiated the adherences observed in groups 1 to 4.…”
Section: Discussionmentioning
confidence: 99%